2013
DOI: 10.1016/j.annemergmed.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility of Rapid Polymerase Chain Reaction-Based Influenza Testing for High-Risk Emergency Department Patients

Abstract: Study objective We evaluate the cost-effectiveness of polymerase chain reaction (PCR)-based rapid influenza testing and treatment for influenza in adult emergency department (ED) patients who are at high risk for or have evidence of influenza-related complications. Methods We developed a cost-utility decision analysis model that assessed adult patients presenting to the ED with symptoms of an acute respiratory infection, who met the Centers for Disease Control and Prevention criteria for recommended antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“…These results support previously reported measurements of pandemic and nonpandemic influenza prevalence rates and the presence of many viral entities simultaneously [26][27][28][29]. These data highlight the need for accurate diagnosis of influenza among hospitalized children receiving oseltamivir, because empiric use may not be cost-effective depending on disease prevalence [30], and reducing unnecessary use would decrease exposure of patients to avoidable medication side effects [31].…”
Section: Discussionsupporting
confidence: 88%
“…These results support previously reported measurements of pandemic and nonpandemic influenza prevalence rates and the presence of many viral entities simultaneously [26][27][28][29]. These data highlight the need for accurate diagnosis of influenza among hospitalized children receiving oseltamivir, because empiric use may not be cost-effective depending on disease prevalence [30], and reducing unnecessary use would decrease exposure of patients to avoidable medication side effects [31].…”
Section: Discussionsupporting
confidence: 88%
“…With routine implementation in high-risk settings, it might be possible to consider a change in policy to test for influenza first before initiating antiviral therapy. However, use of rapid PCR-based influenza testing rather than treatment initiation alone is unlikely to be cost-effective based on drug costs alone, as demonstrated by prior modeling studies [Dugas et al, 2013]. In a typical season at our institution, the cost savings is only $4580; however, this does not include a potential reduction in hospital costs associated with earlier discontinuation of isolation precautions in those with rapid testing, which we were not able to measure in this retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that PCR based rapid testing was the most cost effective strategy although this depended on the prevalence of influenza and again was based on strong assumptions of antiviral use and efficacy. 115 The potential benefits of POC testing for respiratory viruses in adults are listed in Table 3.…”
Section: Other Benefitsmentioning
confidence: 99%